Flame retardants characterization on distribution boxes using thermomechanical and thermogravimetric analysers - Mohd. Zulkefli, Nur Syafiqah Amira (2014)
Fire is the phenomenon in which the liberation of light and heat in consequence with the combustion process which can cause damage, loss of life, loss of belongings and human misery. Earlier investigation concluded that there are many reasons which cause the ignition of fire, partly influenced by low usage of fire retardant materials in our life. Fire retardants are commonly used as components formulated in objects to prevent the start and the spreading of fire. The investigations showed that the highest percentage of fire cases occur in residential area was partly due to the failure of distribution boxes (DB). In this study, a few local brands of DB were characterized based on their manufacture contents and mechanical strength. All samples were analysed through screening test using Fourier Transform Infrared Spectroscopy (FTIR). The results found the samples had similar composition and contain high percentage of acrylonitrile butadiene styrene (ABS), a thermoplastic polymer that is widely used in electrical appliances. Thermomechanical Analyser (TMA) was used to characterize the physical changes of ABS at certain conditions by determining the glass transition, which is the reversible transition in amorphous material from solid state to molten state. The Tg of samples were recorded between 105°C - 110°C and were within the range of ABS transition temperature (104°C - 110°C) that matched with ASTM standard. The thermogravimetric analyser (TGA) measured the sample’s weight loss at linear increase temperature programme. The changes in weight of samples at a range of 420–450 ºC show the degradation value of styrene acrylonitrile (SAN) copolymer in single stage decomposition.